Estudo experimental de um dessalinizador térmico com aquecimento controlado - Rodrigues, Anderson Pereira (2011)
Solar desalination systems operate with a transient heat source, the solar radiation, what makes it difficult to identify of the influence of the process variables and the constructive geometric parameters of the desalination tower. The present work presents the experimental study of thermal a desalination system prototype with heat recovery mechanism and controlled power supply to operate in transient and steady-state regimes. This prototype made possible the study of the operational parameters that influence the desalinated water production in the tower, namely, the height of the water column in the storage tank, the type of burner, the natural gas flow, the number of desalination stages, and the use of a nano film on the condensation surface. Additionally, it was possible to thermally characterize the desalination tower by determining the experimental overall heat transfer coefficient (K1) of the simultaneous evaporation, radiation, and convection processes between the surface of the water in the tank and the condensation walls of the first stage immediately above. The desalination system consisted of a natural gas burning equipment, a tank of storage, and a tower with six desalination stages. By controlling the natural gas flow, it was possible to keep present and constant operating temperatures. The results showed that the use of linear burner (ideal burner) and of 6 liters of water in the tank of storage presented the best desalinated water production. They also showed that the flow of 0.533 g / min of natural gas and the use of 6 or 7 desalination stages are more adequate for tower operation. With the experimental measurements, the determination of the performance coefficient (COP), and of the gain output radio (GOR) was possible. These values were 4.09 and 5.91, respectively. An increase of 65.59% in the desalinated water production was measured with the use of the nano film; however, chemical tests to verify possible chemical contamination were not carried out.